Different from Us: Teaching About the Rich After Occupy and the Great Recession - Ohmann, Richard (Radical Teacher, 2015)
In a famous imaginary exchange, F. Scott Fitzgerald said, "The rich are different from us." Ernest Hemingway replied, "Yes, they have more money." Most critics have thought the epigram attributed to Fitzgerald more perceptive about class in the United States than the one attributed to Hemingway. But if we’re looking for a wry take on how class has been understood, in the media and among college students, Hemingway’s comment is pretty good.